The Effectiveness of Safety Alarm Implementation among Nurses on Fatigue Alarms in Aceh General Hospital's High Care Unit Room - Sri Diana Putri; Teuku Tahlil; Kartini Hasballah (Universitas STRADA Indonesia, 2021)
This study aims to know the effect of implementing the safety alarm protocol among nurses on fatigue alarms in Aceh General Hospital's High Care Unit (HCU) Room. This research is quantitative research with a quasi-experiment model. The sample in this study was all nurses in Aceh General Hospital's High Care Unit room, with a total of 37 respondents. The research instrument was adopted from the Japanese Occupational Hygiene Association and the American Association of Critical-Care Nurses (AACN) Practice Alert. Data analysis used the Wilcoxon Rank test with a 95% confidence level. This study found that fatigue alarm scores decreased significantly after implementing the safety alarm protocol for 21 days (p <0.001). The safety alarm protocol implementation effectively reduces the incidence of fatigue alarm among nurses in Aceh General Hospital's High Care Unit (HCU) room. It means that the safety alarm protocol implementation effectively proved reduces the incidence of fatigue alarms.